Communication during childhood cancer: Systematic review of patient perspectives. Issue 4 (10th December 2019) - Lin, Beryl; Gutman, Talia; Hanson, Camilla S.; Ju, Angela; Manera, Karine; Butow, Phyllis; Cohn, Richard J.; Dalla‐Pozza, Luciano; Greenzang, Katie A.; Mack, Jennifer; Wakefield, Claire E.; Craig, Jonathan C.; et al.
Abstract : Effective communication is challenging in childhood cancer, where decisions carry unpredictable and life‐threatening implications. We aimed to describe patients' experiences of communicating with clinicians during treatment of childhood cancer. A systematic review of qualitative studies to April 2019 was performed. Eligible studies included patients diagnosed with cancer at age ≤ 18 years and reported their perspectives of communicating with clinicians during treatment of childhood cancer. Data were extracted from primary studies for thematic synthesis. From 101 articles across 25 countries involving 1870 participants who were diagnosed with cancer between ages 3 to 18 years, we identified 6 themes: 1) rendered invisible and powerless (displaced and undermined by adult authority; betrayed and distrustful; feeling neglected; helpless and intimidated; disempowered by lack of information); 2) fear and worry for the future (paralyzed by devastating news; uncertainty, anticipation, and dread; broaching intimate and private topics); 3) burdened with responsibility (pressured and unprepared; balancing external expectations; protecting hope); 4) therapeutic patient-provider relationships (emotional support and encouragement; validated personhood and companionship); 5) safety in trust (truthfulness and transparency; prepared by awareness and understanding; reassured by reliable expertise; depending on adults for protection and difficult decisions; security in expressing opinions and needs); and 6) empowerment and assertive agency (right to individual knowledge and choice; control over own life; partnership and respect; enhancing capacity for self‐management). During treatment of childhood cancer, patients gain a sense of respect, safety, and control when they feel clinicians address their information and developmental needs. However, communication that is perceived to be parent‐centered can be disempowering. Promoting child agency and partnership may improve care and outcomes for children with cancer. Abstract : Communication in childhood cancer is particularly challenging; however, most studies focus on familial or physician perspectives rather than those of the child patients. Through a thematic synthesis of 101 articles including 1870 participants, this qualitative review captures child and adolescent experiences, needs, and preferences for communicating with clinicians during childhood cancer to improve strategies for shared decision making.